Preparation method of positive electrode material for improving capacity and cycle performance of lithium battery

By incorporating Ga into the cathode material of lithium batteries and performing calcination treatment, combined with the modification of conductive agents, the stability and cycle life issues of ternary high-nickel materials were solved, and the electrochemical performance of the battery was improved.

CN119297253APending Publication Date: 2025-01-10JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411659093.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Ternary high-nickel materials have problems in lithium batteries, such as unstable surface structure, side reactions with electrolyte, poor cycle stability and thermal stability, which affect the battery capacity and cycle life.

Method used

Modified NCM is formed by mixing NCM with gallium trichloride and polyvinylidene fluoride and calcining it under a nitrogen atmosphere. Ga element is incorporated to expand the cell parameters and enhance the TM-O chemical bond binding energy. At the same time, a three-dimensional conductive network is formed by modifying the conductive agent with a vinyl silane coupling agent to improve the charge transfer at the cathode/electrolyte interface.

Benefits of technology

It improves the cycle stability and capacity of lithium batteries, reduces the risk of structural deformation and collapse during charging and discharging, and enhances the electrochemical performance of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and particularly discloses a preparation method of a positive electrode material for improving the capacity and cycle performance of a lithium battery. Comprising the following operation steps: grinding and mixing NCM, gallium trichloride and polyvinylidene fluoride, calcining in a nitrogen atmosphere to obtain modified NCM, and taking the modified NCM as an active material; the preparation method comprises the following steps: sequentially adding a conductive agent and a vinyl silane coupling agent into 20-30wt% of an ethanol aqueous solution, stirring at 50-60 DEG C for 1-2 hours, and freeze-drying to obtain a vinyl conductive agent; the preparation method comprises the following steps: sequentially adding a vinyl conductive agent, 3-vinyl phenylboronic acid, 4-vinylaniline, N-vinyl pyrrolidone, 1, 3-divinyl-2-imidazolinone and benzoyl peroxide into deionized water, carrying out an oil bath stirring reaction in a nitrogen atmosphere, washing, drying, grinding and sieving to obtain a modified conductive agent; and uniformly mixing the active material, the binder and the conductive agent to obtain the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery. Background Art

[0002] The current new energy market remains thriving, with customers increasingly prioritizing battery energy density. Consequently, ternary high-nickel materials have become a hot topic for many researchers. Market-wide, ternary materials are primarily categorized as NCM and NCA materials. The nickel content determines the battery's charge and discharge capacity, but this also comes with instability. From the perspective of positive electrode materials, increasing nickel content exacerbates Li / Ni mixing in ternary materials, shortening cycle life. Therefore, balancing the high capacity and excellent stability of high-nickel materials has become a new research topic.

[0003] These materials suffer from shortcomings such as unstable surface structures, side reactions with electrolytes, and poor cycling and thermal stability. For example, surface modification, which involves directly forming a layer of stable material on the surface of the bulk material particles to isolate them from direct contact with the electrolyte, is one of the most direct and effective methods for improving material surface stability.

[0004] In summary, it is of great significance to prepare a positive electrode material that improves the capacity and cycle performance of lithium batteries. Summary of the Invention

[0005] The object of the present invention is to provide a method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery comprises the following steps: S1: NCM, gallium trichloride (GaCl3), and polyvinylidene fluoride (PVDF) are ground and mixed, and calcined to obtain modified NCM, which is used as the active material; S2: (1) The active material, binder, and conductive agent are mixed uniformly to obtain a positive electrode slurry; (2) The positive electrode slurry is coated on a current collector and dried to obtain a positive electrode material.

[0007] In the scheme, the addition of Ga elements can not only expand the unit cell parameters, but also achieve a stronger binding energy of the TM-O chemical bond by controlling the Ga content in NCM, thereby reducing the risk of deformation and collapse of the NCM lattice structure during charge and discharge, and improving the battery cycle stability; Cl and O have similar atomic radii and can easily replace the position of O in the material, thereby improving the stability of the structure and increasing the cycle life; PVDF powder will undergo molecular chain rupture at high temperatures, and the generated F- It will also increase the stability of the material; calcination in a N2 atmosphere reduces the distribution of oxygen vacancies, alleviates the defect of easy collapse of the high-nickel material structure after multiple charges and discharges, and further improves the cycle stability.

[0008] The more optimized mass ratio of NCM to gallium trichloride is (40~45):1; the mass ratio of NCM to polyvinylidene fluoride is (55~60):1.

[0009] The more optimized calcination process parameters are: calcination at a temperature of 350°C to 400°C for 12 hours under a nitrogen atmosphere; wherein the calcination heating rate is 20°C / min to 22°C / min, and the calcination annealing rate is 12°C / min to 15°C / min.

[0010] More optimally, in the positive electrode slurry, the mass ratio of the active material, the binder, and the conductive agent is 95.8:2.2:2.0.

[0011] More optimally, the current collector includes but is not limited to aluminum foil; the binder includes but is not limited to PVDF; the conductive agent includes but is not limited to SuperP.

[0012] More optimally, the conductive agent is modified in advance to obtain a modified conductive agent; the modification process is: (1) Adding a conductive agent and a vinyl silane coupling agent to a 20-30 wt% ethanol aqueous solution in sequence, stirring at 50-60° C. for 1-2 hours, and freeze-drying to obtain a vinyl conductive agent; (2) Vinyl conductive agent, 3-vinylphenylboronic acid, 4-vinylaniline, N-vinylpyrrolidone, 1,3-divinyl-2-imidazolidinone, and benzoyl peroxide are sequentially added to deionized water, stirred in an oil bath at 98-102°C under a nitrogen atmosphere for 8-10 hours, washed, dried, ground, and sieved to obtain a modified conductive agent.

[0013] More optimally, in the vinyl conductive agent, the mass ratio of the conductive agent to the vinyl silane coupling agent is 1:0.2~0.3.

[0014] More optimally, the modified conductive agent includes the following raw materials in parts by mass: 2 to 2.5 parts of vinyl conductive agent, 2 to 2.5 parts of 3-vinylbenzeneboric acid, 0.5 to 0.7 parts of 4-vinylaniline, 30 to 40 parts of N-vinylpyrrolidone, 0.6 to 0.8 parts of 1,3-divinyl-2-imidazolidinone, and 0.12 to 0.15 parts of benzoyl peroxide.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention grinds and mixes NCM, gallium trichloride, and polyvinylidene fluoride until uniform, and calcines them under a nitrogen atmosphere to obtain modified NCM, which is used as an active material; In this scheme, the incorporation of Ga elements can not only expand the unit cell parameters, but also achieve a stronger binding energy of the TM-O chemical bond by controlling the Ga content in NCM, thereby reducing the risk of deformation and collapse of the NCM lattice structure during charge and discharge, and improving the battery cycle stability; Cl - The ionic radius is slightly larger than that of O 2- , causing the NCM lattice to expand slightly, which is beneficial to expand the Li + transmission channel, thereby increasing capacity. - The ionic radius is smaller than that of O 2- , cannot reach Cl - The role of doping, Br - and I - The ionic radius is much larger than that of O 2- , after doping, it will affect the structural changes of the original material and affect the performance of the battery end; therefore, the combination of polyvinylidene fluoride and N2 in the scheme can further improve the cycle stability of the material at the battery end.

[0016] In order to further improve the electrochemical properties of the battery, the present invention modifies the surface of the conductive agent by using a vinyl silane coupling agent, and then reacts it with 3-vinylphenylboronic acid, 4-vinylaniline, N-vinylpyrrolidone, and 1,3-divinyl-2-imidazolidinone to obtain a modified conductive agent.

[0017] In the scheme, the amine group on 4-vinylaniline can increase the polarity of the conductive polymer, and the electron donor property of the amine group can improve the conductivity of the conductive polymer; 1,3-divinyl-2-imidazolidinone can improve the stability and cross-linking degree of the conductive polymer; and N-vinylpyrrolidone is a linear polymer that can increase the flexibility and water resistance of the conductive agent; after it undergoes polymerization reaction with 3-vinylphenylboronic acid, 4-vinylaniline, and N-vinylpyrrolidone, a conductive polymer with a three-dimensional conductive network is formed on the surface of the conductive agent, thereby improving the charge transfer at the positive electrode / electrolyte interface; and the conductive polymer can adapt to volume changes and reduce crack formation.

[0018] In the scheme, the hydroxyl groups in the boric acid on 3-vinylphenylboronic acid form hydrogen bonds with the metal ions or oxygen ions on the surface of the modified NCM811, thereby promoting the interaction between the modified conductive agent and the modified NCM811, and increasing the direct contact area between the positive electrode material and the electrolyte, thereby achieving the cycle stability of the battery. DETAILED DESCRIPTION

[0019] The following describes preferred implementations of the present invention. Obviously, the described embodiments are only a portion of the embodiments of the present invention, not all of them. It will be apparent to those skilled in the art that all other implementations derived without inventive effort, without departing from the principles of the present invention, are within the scope of protection of the present invention.

[0020] In the following specific embodiments, parts are by mass. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions. Examples include: NCM is NCM811, product number PA91222, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; the CAS number of gallium trichloride is 13450-90-3, purchased from Sichuan Polypure Material Technology Co., Ltd.; the CAS number of polyvinylidene fluoride (PVDF) is 24937-79-9, purchased from Wuhan Rongcan Biotechnology Co., Ltd.; the CAS number of N-vinyl pyrrolidone is 88-12-0, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the CAS number of 3-vinylphenylboronic acid is 15016-43-0, purchased from He Peng (Shanghai) Biotechnology Co., Ltd.; the CAS number of 4-vinylaniline is 1520-21-4, purchased from Hubei Xin Hongli Chemical Co., Ltd.; the CAS number of 1,3-divinyl-2-imidazolidinone is 13811-50-2, purchased from Zhengzhou Aikemu Chemical Co., Ltd. Example

[0021] S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0022] Example 2 is based on Example 1, and the mass ratio of NCM811 to GaCl3 is 35:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 35:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0023] Example 3 is based on Example 1, and the mass ratio of NCM811 to GaCl3 is 40:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 40:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0024] Example 4 is based on Example 1, and the mass ratio of NCM811 to GaCl3 is 50:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 50:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0025] Example 5 Based on Example 1, the mass ratio of NCM811 to GaCl3 is 55:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 55:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0026] Example 6 Based on Example 1, the mass ratio of NCM811 to polyvinylidene fluoride is 50:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 50:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0027] Example 7 is based on Example 1, and the mass ratio of NCM811 to polyvinylidene fluoride is 55:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 55:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0028] Example 8 is based on Example 1, except that the mass ratio of NCM811 to polyvinylidene fluoride is 65:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 65:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0029] Example 9 is based on Example 1, except that the mass ratio of NCM811 to polyvinylidene fluoride is 70:1; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 70:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0030] Example 10 is based on Example 1, and the conductive agent is modified; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) adding a conductive agent (Super P) and a vinyl silane coupling agent to a 25 wt% ethanol aqueous solution in sequence, stirring at 55°C for 1.5 hours, and freeze-drying to obtain a vinyl conductive agent; wherein the mass ratio of the conductive agent (Super P) to the vinyl silane coupling agent is 1:0.25; (2) 2.5 parts of a vinyl conductive agent, 2 parts of 3-vinylphenylboric acid, 0.5 parts of 4-vinylaniline, 30 parts of N-vinylpyrrolidone, 0.6 parts of 1,3-divinyl-2-imidazolidinone, and 0.12 parts of benzoyl peroxide were sequentially added to deionized water, stirred in an oil bath at 100°C under a nitrogen atmosphere for 8 hours, washed, dried, ground, and sieved to obtain a modified conductive agent; S3: (1) The active material, binder (Solvay 5130), and modified conductive agent were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0031] Comparative Example 1 is based on Example 1, except that no GaCl3 is introduced into S1; S1: NCM811 and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0032] Comparative Example 2 is based on Example 1, except that no polyvinylidene fluoride is introduced into S1; S1: Grind and mix NCM811 and GaCl3 until uniform, transfer them to a magnetic boat, and calcine them at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which is used as the active material; wherein the mass ratio of NCM811 to GaCl3 is 45:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0033] Comparative Example 3 is based on Example 1, except that S1 is calcined in air; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C for 12 hours in a tube furnace with air to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) The active material, binder (Solvay 5130), and conductive agent (Super P) were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0034] Comparative Example 4 is based on Example 1, using traditional NCM811 material as the active material; (1) The active material, binder (Solvay 5130), and conductive agent were weighed in a mass ratio of 95.8:2.2:2.0 and mixed uniformly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130°C for 12 hours to obtain a positive electrode material.

[0035] Comparative Example 5 was based on Example 10, but without the introduction of 3-vinylphenylboronic acid; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) adding a conductive agent (Super P) and a vinyl silane coupling agent to a 25 wt% ethanol aqueous solution in sequence, stirring at 55°C for 1.5 hours, and freeze-drying to obtain a vinyl conductive agent; wherein the mass ratio of the conductive agent to the vinyl silane coupling agent is 1:0.25; (2) 2.5 parts of a vinyl conductive agent, 0.5 parts of 4-vinylaniline, 30 parts of N-vinylpyrrolidone, 0.6 parts of 1,3-divinyl-2-imidazolidinone, and 0.12 parts of benzoyl peroxide were sequentially added to deionized water, stirred in an oil bath at 100°C under a nitrogen atmosphere for 8 hours, washed, dried, ground, and sieved to obtain a modified conductive agent; S3: (1) The active material, binder (Solvay 5130), and modified conductive agent were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0036] Comparative Example 6 is based on Example 10, except that N-vinyl pyrrolidone is introduced alone; S1: NCM811, GaCl3, and polyvinylidene fluoride were ground and mixed until uniform, transferred to a magnetic boat, and calcined at 400°C in a tube furnace under nitrogen for 12 hours to obtain modified NCM811, which was used as the active material; wherein the mass ratio of NCM811 to GaCl3 was 45:1, and the mass ratio of NCM811 to polyvinylidene fluoride was 60:1; S2: (1) adding a conductive agent (Super P) and a vinyl silane coupling agent to a 25 wt% ethanol aqueous solution in sequence, stirring at 55°C for 1.5 hours, and freeze-drying to obtain a vinyl conductive agent; wherein the mass ratio of the conductive agent (Super P) to the vinyl silane coupling agent is 1:0.25; (2) 2.5 parts of a vinyl conductive agent, 30 parts of N-vinyl pyrrolidone, 0.6 parts of 1,3-divinyl-2-imidazolidinone, and 0.12 parts of benzoyl peroxide were sequentially added to deionized water, stirred in an oil bath at 100°C under a nitrogen atmosphere for 8 hours, washed, dried, ground, and sieved to obtain a modified conductive agent; S3: (1) The active material, binder (Solvay 5130), and modified conductive agent were weighed in a mass ratio of 95.8:2.2:2.0 and mixed evenly to obtain a positive electrode slurry; (2) The positive electrode slurry was coated on a 15 μm aluminum foil and dried in a vacuum drying oven at 130 °C for 12 hours to obtain a positive electrode material.

[0037] Test experiment 1: (1) The positive electrode materials of Examples 1 to 10 and Comparative Examples 1 to 6 were coated on 15 μm aluminum foil respectively, and dried at 130°C in a vacuum drying oven for 12 hours to obtain positive electrode plates; the button battery shell was selected as CR2032 model, the diaphragm was selected as 16 μm diaphragm, and the plate was selected as the positive electrode plate with uniform coating. In a glove box filled with argon, the button battery was assembled in the following order: battery shell - placing positive electrode plate - dripping electrolyte - placing diaphragm - dripping electrolyte - placing lithium plate - placing gasket spring - battery shell.

[0038] (2) Test of the first charge and discharge efficiency: The button battery was charged and discharged at 0.2C using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A) with a voltage range of 2.7–4.25V. The test results are shown in Table 1.

[0039] (3) Cyclic performance test: A button cell charge and discharge tester (Wuhan Blue Electric, CT2001A) was used to perform 50 cycles of 0.2C charge and discharge tests on the button cells with a voltage range of 2.7–4.25 V. The test results are shown in Table 1.

[0040] Table 1

[0041] Conclusion: When modified NCM811 is used as the active material, as can be seen from Examples 1-9 and Comparative Examples 1-4, the electrochemical performance of the battery is improved after calcining and modifying NCM811 with gallium trichloride and polyvinylidene fluoride. Furthermore, the study found that in Example 1, the electrochemical performance of the battery was optimal when the mass ratio of modified NCM811 to gallium trichloride was 45:1, and the mass ratio of modified NCM811 to polyvinylidene fluoride was 60:1. Example 10, based on Example 1, modified the conductive agent. The study found that the electrochemical performance of the battery was improved because the conductive polymer formed on the surface of the conductive agent can improve charge transfer at the positive electrode / electrolyte interface. Furthermore, the conductive polymer can adapt to volume changes and reduce crack formation.

[0042] Comparative Example 5 is based on Example 10, but without the introduction of 3-vinylphenylboronic acid. This reduces the interaction between the modified conductive agent and the modified NCM811 because the hydroxyl groups in the boric acid on 3-vinylphenylboronic acid form hydrogen bonds with metal ions or oxygen ions on the surface of the modified NCM811, thereby achieving improved battery cycling stability. Comparative Example 6 is based on Example 10, but with the introduction of N-vinylpyrrolidone alone. N-vinylpyrrolidone can undergo polymerization with 3-vinylphenylboronic acid and 4-vinylaniline to form a three-dimensional conductive network. However, N-vinylpyrrolidone is a linear polymer, and after reacting with the modified conductive agent, the resulting conductive polymer has reduced performance, thereby reducing the electrochemical performance of the battery.

[0043] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention, but the scope of protection of this application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the spirit and principles of the present invention and within the technical scope disclosed in this application should be included in the scope of protection of this application. The embodiments and features of the embodiments of this application can be combined with each other unless there is a conflict. Therefore, the scope of protection of this application should be based on the scope of protection of the claims.

Claims

1. A method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery, characterized in that: The steps include: S1: grinding and mixing NCM, gallium trichloride and polyvinylidene fluoride, and calcining to obtain modified NCM, which is used as an active material; S2: (1) Evenly mix the active material, binder and conductive agent to obtain positive electrode slurry; (2) Coat the positive electrode slurry on the current collector and dry it to obtain the positive electrode material.

2. A method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery according to claim 1, characterized in that: The mass ratio of NCM to gallium trichloride is (40-45):1; the mass ratio of NCM to polyvinylidene fluoride is (55-60):

1.

3. The method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery according to claim 1, characterized in that: The calcination process parameters are: calcination at a temperature of 350-400°C for 12 hours in an inert gas atmosphere; wherein the calcination heating rate is 20°C / min-22°C / min, and the calcination annealing rate is 12°C / min-15°C / min.

4. The method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery according to claim 1, characterized in that: In the positive electrode slurry, the mass ratio of active material, binder and conductive agent is 95.8:2.2:2.

0.

5. The method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery according to claim 1, characterized in that: The current collector includes aluminum foil; the binder includes PVDF; and the conductive agent includes SuperP.

6. The method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery according to claim 1, characterized in that: The conductive agent is pre-modified to obtain a modified conductive agent; the modification process is: (1) adding a conductive agent and a vinyl silane coupling agent to a 20-30 wt% ethanol aqueous solution in sequence, stirring at 50-60° C. for 1-2 hours, and freeze-drying to obtain a vinyl conductive agent; (2) A vinyl conductive agent, 3-vinylbenzene boronic acid, 4-vinylaniline, N-vinyl pyrrolidone, 1,3-divinyl-2-imidazolidinone, and benzoyl peroxide are sequentially added into deionized water, stirred in an oil bath at 98-102° C. under a nitrogen atmosphere for 8-10 hours, washed, dried, ground, and sieved to obtain a modified conductive agent.

7. The method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery according to claim 1, characterized in that: In the vinyl conductive agent, the mass ratio of the conductive agent to the vinyl silane coupling agent is 1:0.2-0.

3.

8. The method for preparing a positive electrode material for improving the capacity and cycle performance of a lithium battery according to claim 1, characterized in that: The modified conductive agent includes the following raw materials in parts by weight: 2 to 2.5 parts of vinyl conductive agent, 2 to 2.5 parts of 3-vinylbenzeneboric acid, 0.5 to 0.7 parts of 4-vinylaniline, 30 to 40 parts of N-vinylpyrrolidone, 0.6 to 0.8 parts of 1,3-divinyl-2-imidazolidinone, and 0.12 to 0.15 parts of benzoyl peroxide.

Citation Information

Cited By

  • Lithium battery pack with excellent cycle performance and preparation method thereof

    CN120015949A